A high‐order numerical method for sediment transport problems simulation and its comparison with laboratory experiments. Issue 6 (23rd February 2021) - Capilla Romá, María Teresa; Balaguer‐Beser, Angel; Nácher‐Rodríguez, Beatriz; Vallés‐Morán, Francisco J.
Abstract: This article describes a high‐order well‐balanced central finite volume scheme for solving the coupled Exner−shallow water equations in one dimensional channels with rectangular section and variable width. Such numerical method may solve the proposed bedload sediment transport problem without the need to diagonalize the Jacobian matrix of flow. The numerical scheme uses a Runge–Kutta method with a fourth‐order continuous natural extension for time discretization. The source term approximation is designed to verify the exact conservation property. Comparison of the numerical results for two accuracy tests have proved the stability and accuracy of the scheme. The results of the laboratory tests have also been used to calibrate different expressions of the solid transport discharge in the computer code. Two experimental tests have been carried out to study the erosive phenomenon and the consequent sediment transport: one test consisting of a triangular dune, and other caused by the effect of channel contraction.